Bis(N-benzyl-N-methyldithiocarbamato-κ2S,S′)(pyridine-κN)cadmium(II) - Ehsan, Muhammad Ali; Muhammad Mazhar,; Tiekink, Edward R. T. * (International Union of Crystallography, 2016)
The title compound, [Cd(C9H10NS2)2(C5H5N)], features a five-coordinate CdII atom, being coordinated by two nearly symmetrically chelating dithiocarbamate ligands and a pyridine N atom. The resulting NS4 donor set defines a distorted coordination geometry tending toward square pyramidal. In the molecular packing, centrosymmetric ten-membered {...HCNCS}2 synthons arise as a result of methylene-C-H...S interactions. These are connected into layers parallel to (10-2) via weak methyl-C-H...[pi](phenyl) interactions.